ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI HARGA SAHAM MELALUI STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2020-2022 - Azizah, Faradila Alya Nur; Wahyuni, Ika; Ariyantiningsih, Febri (Fakultas Ekonomi dan Bisnis, 2024)
The aim of this research is to analyze the factors that influence share prices through capital structure. The aim of this research is to analyze the factors that influence share prices through capital structure. This research applies quantitative methods in the research process. The sampling technique used in the research is purposive sampling technique. The results of the direct influence test using the Smart PLS 3.0 application show that Sales growth has a significant negative influence on Capital structure, Profitability has a significant positive influence on Capital structure, Asset structure has a significant negative influence on Capital structure, Sales growth has a positive but not significant influence on Share prices, Profitability has a negative but insignificant influence on Share prices, Asset structure has a significant positive influence on Share prices, and Capital structure has a significant positive influence on Share prices. The findings from the indirect analysis show that Sales growth has a negative but insignificant influence on Share prices through Capital structure, Profitability has a positive but insignificant influence on Share prices through Capital structure, and Asset structure has a negative but insignificant influence on Share prices through Capital structure.